Povo Boe : memórias silenciosas e educação no Vale do Rio Cuiabá - Oliveira, Itamara dos Anjos (2023)
The aim of this narrative is to present the results of the research carried out to understand the historicity of the Boe people in the construction of the territory known as the Vale do Rio Cuiabá, in different temporalities, and its expression in the identity of Cuiabá. To this end, we sought to investigate how the cultural interaction between the inhabitants of the Vale do Rio Cuiabá and the Boe people contributed to the richness of the territoriality studied, and to explore the decolonial perspective and interculturality in pedagogy, analysing how the cultural practices of the Vale do Rio Cuiabá can enrich pedagogical practice. The methodological approach chosen to write the text was based on the concepts of the method proposed by the historian Carlo Ginzburg (1989, 2001, 2002, 2004, 2006), the indicative paradigm, to analyse historical sources related to the Boe people in different periods, seeking in the texts analysed to find information that goes beyond what has already been revealed, giving meanings to the writings that allow us to obtain data that go beyond the perspective of recognizing them only as details or part of a narrative, in order to understand the society that produced them, respecting the time frames of each era. To overcome the official monocultural perspective, the sources for the study were books, websites, theses, dissertations, and observations made in the more traditional contexts of local culture, all of which provided theoretical support and evidence for the construction of the historical pedagogical narrative presented. The results showed the considerable influence of the Boe people in the construction of Cuiabá's identity and the characteristics that define Cuiabania today. In this context, it was concluded not only that interculturality and decolonial pedagogy are important in promoting education that gives visibility to protagonists erased in official history, but also that it was possible to highlight the relevant contributions of the Boe people's knowledge to the understanding of the different forms of knowledge and cultural practices that can constitute educational knowledge and practices in the school context.